Hubungan Usia Dan Klasifikasi Operasi Dengan Tingkat Kecemasan Pada Pasien Pre Operasi Elektif Dirumah Sakit Lavalette Malang - Ainul Haqi Fatkhul K.A, Moh; Widodo, Dyah; Marsaid; Budi Pertami, Sumirah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: To examine the correlation between preoperative elective surgery patients' anxiety levels and their age in relation to the classification of operation at Lavalette Hospital Malang. Methods: This research design employs a descriptive-correlational quantitative approach using cross-sectional methods. The sampling method uses nonprobability sampling of the purposive sampling type, involving preoperative elective surgery patients in the Surgical Inpatient Ward of Lavalette Hospital Malang, with a total of 66 respondents. Results: The study's results indicated that the anxiety levels of most preoperative elective surgery patients were severe. Most respondents underwent major surgery and were aged 46-65 years. For the variables of age and anxiety levels, the Spearman's rank test revealed a pvalue of 0.001 and a correlation coefficient of -0.396. For the variables of operation categorization and anxiety levels, the pvalue was 0.017 and the correlation coefficient was 0.293. Conclusion: The study concludes that anxiety levels in preoperative elective surgery patients at Lavalette Hospital Malang are correlated with age and surgery categorization. It is hoped that healthcare professionals, especially nurses, will monitor the anxiety levels of preoperative patients to facilitate smoother preoperative procedures.